Reassessment of the species “Podocnemis” brasiliensis Staesche, 1937 (Testudines, Pleurodira, Pelomedusoides) - Diniz, Joaquin Pedro Bogado (2024)
The Bauru Group is a sedimentary sequence of the Paraná Basin, dated to the Late Cretaceous. Its palaeofaunistical assemblage includes a rich record of turtles of the lineage Podocnemidoidae, but many of the taxa that have been described from this geologic unit have an uncertain taxonomy. An example is the species “Podocnemis” brasiliensis, known from a single fragmentary plastron and regarded by many authors as a nomen dubium. The discovery of specimen FFP PG 218, comparable to “Podocnemis” brasiliensis, permitted the attribution of this specimen to this taxon, adding to its hypodigm. The new fossil preserves anatomical parts that are lacking in the type specimen of “P.” brasiliensis, permitting an amendment to the species’ diagnosis, with the addition of new diagnostic characteristics. With the new diagnosis, it was possible to revisit specimens that had been attributed to the species “P.” brasiliensis in the past, and assess whether they could really be attributed to this taxon. The revision showed that none of the past attributions can be confirmed. However, there are two occurrences of specimens similar to “P.” brasiliensis that were compared to this species through the use of open taxonomy modifiers, indicating the uncertainty behind these associations. A geometric morphometric analysis was performed using the epiplastra of the turtles of the Bauru Group, with the aim of evaluating the shape variation of this structure. The analysis recovered considerable variation described by three principal components, linked mainly to changes in the width of the intergular scute and the length of the epiplastron as a whole. The morphometric analysis also corroborated the current taxonomy of Bauru Group forms, organizing the sampled individuals in a way similar to the previously proposed taxonomic groupings, with “P.” brasiliensis appearing as a distinct taxon. To assess the relevance of shell thickness as a diagnostic characteristic in alpha- taxonomy, correlation tests and linear regressions were run using a sample of living and extinct Podocnemidoidae, as well as subsets for three taxa of the Bauru Group. It was not possible to make a subset out of “P.” brasiliensis due to the small number of available specimens. The analysis indicated that the shell of Roxochelys wanderleyi is proportionally thicker than that of other Podocnemidoidae. Still, the results show that the proportional thickness of the shell exhibits considerable intra- specific variation, and that the allometric effect of the regressions recovered from the whole sample and the subsets is rather subtle, not very different from isometry. Keywords: podocnemidoidae; bauru group; geometric morphometric analysis; epiplastron; shell thickness; alpha-taxonomy